1971
DOI: 10.1007/bf00056084
|View full text |Cite
|
Sign up to set email alerts
|

Fifth supplementary list of wheat varieties classified according to their genotype for hybrid necrosis and geographical distribution of Ne-genes

Abstract: An account is given about the progress in the work of the last two years . Further work is being done on the geographical distribution of both the Ne-genes .The fifth supplement consists of 144 Ne t -carriers, 208 Ne e -carriers and 326 noncarriers, together 678 varieties . The total number of varieties is 2513 being 597 Ne,-(23 .8 %), 654 Ne e -(26 .0 %) and 1262 (50 .2 %) non-carriers .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1972
1972
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…In contrast to our findings, Zeven (1971) reported the following two non-carrier regions besides the one we found in Central Asia; these include, (I). Southern GreeceMediterranean Islands -Southern Italy -Eastern and Southern Spain -North Africa -Sahara and (II) Norway -Sweden -Denmark -Poland -France -Germany -Switzerland -Austria -Hungary -Yugoslavia.…”
Section: Non-carrier Regionscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Zeven (1971) reported the following two non-carrier regions besides the one we found in Central Asia; these include, (I). Southern GreeceMediterranean Islands -Southern Italy -Eastern and Southern Spain -North Africa -Sahara and (II) Norway -Sweden -Denmark -Poland -France -Germany -Switzerland -Austria -Hungary -Yugoslavia.…”
Section: Non-carrier Regionscontrasting
confidence: 99%
“…These local clean spots, called non-carrier regions by Zeven (1971), have been found in Central Asia (Pakistan, Afghanistan, Central and South Iran), and in Northern Europe (Norway, Sweden and Finland) (Tsunewaki and Nakai 1967a;Tsunewaki and Honi 1967). The current results suggest the presence of a third noncarrier region in the Balkan Peninsula.…”
Section: Non-carrier Regionsmentioning
confidence: 99%
“…reported that wheats possessing Lrl3 always carried the hybrid necrosis allele, Ne2m, and that crosses involving such wheats and Line E usually, but not always, segregated in F2 for hybrid necrosis. Because the F1 of the Line E crosses did not show symptoms of hybrid necrosis, the majority Line E genotype was postulated to be Nelw which is common in cultivars of Australian origin(ZEVEN, 1971). However, some plants of Line E were found to be nelnel.…”
mentioning
confidence: 99%
“…assigned live alleles to the Ne, locus. Two cultivars involved in the pedigree of Tobari 66 carry the allele Nelm, Lerma Rojo (ZEVEN, 1971) and Frontana ). However, it has been well documented that the degree of necrosis can be affected by environment ZEVEN, 1976).…”
Section: Discussionmentioning
confidence: 99%